2012
DOI: 10.1159/000334968
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Neurofibromatosis Type 2 Gene Promoter Methylation in Sporadic Vestibular Schwannomas

Abstract: Background: Vestibular schwannomas (VS) are benign tumors of the nervous system that are usually sporadic but also occur in the inherited disorder neurofibromatosis type 2 (NF2). In VS, losses of chromosomal material and mutations of the NF2 gene have been established to be causative. For a subset of VS without detectable gene alterations, promoter inactivation by hypermethylation has been suggested. However, published data are very limited and contradictory. Methods: We analyzed NF2 gene promoter methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…For the rest of the cases, one might speculate on other causes of impairment of normal merlin function, including epigenetic silencing, post-translational modifications, impairment of RNA splicing, or hits in related pathways and molecules, although epigenetic silencing of NF2 does not seem to be a prevalent event. 25,26 Another issue to address is the allelic frequency by which the mutations in NF2 occur. If we use VS10 as an illustrative example, one can identify a mutation in both exons 4 and 10 with allelic fractions of 19% and 22%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For the rest of the cases, one might speculate on other causes of impairment of normal merlin function, including epigenetic silencing, post-translational modifications, impairment of RNA splicing, or hits in related pathways and molecules, although epigenetic silencing of NF2 does not seem to be a prevalent event. 25,26 Another issue to address is the allelic frequency by which the mutations in NF2 occur. If we use VS10 as an illustrative example, one can identify a mutation in both exons 4 and 10 with allelic fractions of 19% and 22%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to non-head and neck schwannomas, sporadic vestibular schwannomas have shown no mutations on BRAF , EGFR , PIK3CA or KRAS [8]. Controversial findings on epigenetic aberrant methylation of NF2 in schwannomas have been provided [9][12], and data on promoter methylation of tumor-related genes have also been described [13]. The NF2 gene encodes for Merlin or Schwannomin [14], [15], a protein that shares sequence homology with members of the ezrin/radixin/moesin (ERM) family.…”
Section: Introductionmentioning
confidence: 99%
“…35 reported that the site-specific methylation of the promotor elements was important for NF2 silencing in sporadic VSs. However, another three studies that included 93 sporadic VSs detected no aberrant methylation of the NF2 gene in any tumours 8, 36, 37 , suggesting that promoter methylation is an uncommon mechanism of NF2 inactivation in sporadic VSs.…”
Section: Discussionmentioning
confidence: 92%